Rural Household Savings and Financial Inclusion as Determinants of Sustainable Rural Economic Growth in Nigeria - Abubakar, Bello Bunza; Illo, A. I. (Academia Journal of Humanities & Social Sciences, 2026)
This study investigated the determinants of savings among rural households in Kebbi State, Nigeria, using data from 240 respondents selected through a multi-stage random sampling technique across 16 villages in 4 LGAs. Data were collected using structured questionnaires and analyzed with descriptive statistics and linear regression models. The results revealed that most respondents (31.7%) were aged 41–50 years, 75% were married, and 84.2% were male. Households were typically large (66.7% had 6–10 members), with 32.1% having 10–20 years of farming experience. Annual incomes for 58.7% of respondents ranged between ₦120,001 and ₦240,000, with crop farming as the primary occupation (53.3%). Land was mostly inherited (56.7%), and farm sizes were generally small (1–5 hectares). while 41.7% traveled 11–20 km to access financial institutions. The regression results showed that interest rates and expenditure had significant positive effects on savings, whereas distance to banks negatively influenced savings. Low savings capacity emerged as the main barrier, as resources barely covered basic needs. The study recommends diversifying income sources and expanding rural banking infrastructure to stimulate savings culture and financial inclusion.